Comparison of EASYPREP® and SurePath® in thyroid fine‐needle aspiration. Issue 4 (5th February 2016) - Chong, Yosep; Baek, Ki Hyun; Kim, Jee Young; Kim, Tae‐Jung; Lee, Eun Jung; Kang, Chang Suk
Abstract : Background: While fine‐needle aspiration cytology (FNAC) using conventional smear has been widely accepted as the primary diagnostic tool for thyroid lesions, liquid‐based preparations (LBPs) are increasingly replacing it. A new automated LBP method, EASYPREP ® (EP), was recently introduced and has shown relevant diagnostic efficacy in gynecologic samples. We compared the diagnostic utility of EP and SurePath ® (SP), a more widely established LBP method, in thyroid FNAC. Methods: Under the ultrasonographic guidance, 253 thyroid FNAC samples were collected by sample‐splitting manner. Three pathologists made cytologic diagnoses of EP and SP according to the Bethesda system independently and compared the cytomorphologic parameters. Cytohistologic correlation was performed in 30 resected cases. Results: Fifteen (5.9%) and 21 (8.3%) samples were unsatisfactory in SP and EP, respectively, owing to the unequal sample‐splitting. Cytologic diagnoses of SP and EP were consistent in 228 cases (90.1%), and inconsistent in remainder mostly owing to the unequal distribution of pathognomic cells. While cytomorphologic parameters were not significantly different between two methods, EP showed less three‐dimensional configuration in benign lesions. Cytohistologic correlation showed no significant differences in sensitivity (100% vs. 95.5%) and specificity (100% vs. 100%) between SP and EP. Labor time for processing 48 cases was 42% shorter with EP than with SP (28 min vs. 48 min). Conclusions: The diagnostic utility of EP in thyroid FNAC was comparable to that of SP. EP allowed better visibility owing to better fragmentation of follicular clusters. The automated system of EP has the advantages of a shorter labor time for batch processing. Diagn. Cytopathol. 2016;44:283–290. © 2016 Wiley Periodicals, Inc.